Levosimendan‐induced venodilation is mediated by opening of potassium channels. (30th October 2021) - Burkhoff, Daniel; Rich, Stuart; Pollesello, Piero; Papp, Zoltán
Abstract: Unique vascular responses adhere to the cardiovascular efficacy of the inodilator levosimendan. In particular, selective venodilation appears to explain its clinical benefit during pulmonary hypertension complicated by heart failure with preserved ejection fraction. Vasodilators increase vessel diameter in various parts of the vascular system to different degrees and thereby influence blood pressure, its distribution, and organ perfusion depending on their mechanisms of action. Levosimendan and its long‐lived active metabolite OR‐1896 mobilize a set of vasodilatory mechanisms, that is, the opening of the ATP‐sensitive K + channels and other K + channels on top of a highly selective inhibition of the phosphodiesterase III enzyme. A vessel‐specific combination of the above vasodilator mechanisms—in concert with cardiac effects and cardiovascular reflex regulations—illustrates the pharmacological profile of levosimendan in various cardiovascular disorders. While levosimendan has been known to be an inotrope, its properties as an activator of ATP‐sensitive K + channels have gone largely ignored with respect to clinical applications. Here, we provide a summary of what is known about the ATP‐sensitive K + channel properties in preclinical studies and now for the first time, its ATP‐sensitive K + channel properties in a clinical trial.